Serum selenium and subsequent risk of cancer among Finnish men and women. - Knekt, P; Aromaa, A; Maatela, J; Alfthan, G; Aaran, R; Hakama, M; Hakulinen, T; Peto, R; Teppo, L (1990)
The association between the serum selenium level and the subsequent incidence of cancer was investigated in a longitudinal study of 39,268 men and women participating in the Social Insurance Institution's Mobile Clinic Health Examination Survey in Finland. The baseline examinations, including the collection of blood samples, were performed in 1968-1972. During a median follow-up of 10 years, 1,096 new cancer cases were identified from the files of the Finnish Cancer Registry. Selenium concentrations were measured from the stored serum samples collected from these cancer cases and from two controls per case, matched for sex, municipality, and age. The mean serum selenium level was 59.1 micrograms/L among all male cancer cases and 62.5 micrograms/L among controls. The difference was statistically significant (P less than .001). Corresponding values among women were 63.6 and 63.9 micrograms/L, respectively. Low serum selenium levels were associated with an increased risk of developing cancer at several sites, especially cancers of the stomach and lung among men. The relative risk of lung cancer between the highest and lowest decile of serum selenium was 0.11, and it differed significantly from unity (P less than .001). These findings are in agreement with the hypothesis that low selenium intake may increase the risk of some cancers among men.